2014
DOI: 10.1051/0004-6361/201323249
|View full text |Cite
|
Sign up to set email alerts
|

New experimental sublimation energy measurements for some relevant astrophysical ices

Abstract: Context. The knowledge of the sublimation energy of ices allows us to better understand the dynamics between surfaces and atmospheres of different environments of astrophysical interest where ices are present. Aims. This work is intended to provide sublimation energy values for a set of pure ices (CO, CH 4 , CO 2 , N 2 , and NH 3 ) using a new experimental procedure. The results were compared to some values obtained by other authors under different conditions and/or methods, to check the reliability of this ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
2
23
1
Order By: Relevance
“…• CO, as an example of a volatile species, with a 7.3 kJ/mol desorption energy much less than that of water (Collings & McCoustra 2005;Luna et al 2014), experiences a first desorption from a water ice mixture at temperatures of 20-60 K, in agreement with its small desorption energy. A very small molecule like CO can also diffuse into the ice as it is slowly heated.…”
Section: Comet Grain Modelmentioning
confidence: 66%
See 1 more Smart Citation
“…• CO, as an example of a volatile species, with a 7.3 kJ/mol desorption energy much less than that of water (Collings & McCoustra 2005;Luna et al 2014), experiences a first desorption from a water ice mixture at temperatures of 20-60 K, in agreement with its small desorption energy. A very small molecule like CO can also diffuse into the ice as it is slowly heated.…”
Section: Comet Grain Modelmentioning
confidence: 66%
“…• Species like CO 2 , with a desorption energy of 26 kJ/mol still less volatile than water (Luna et al 2014) but too large to diffuse into the ice, show multi-layer desorption in a broad temperature range around 80 K, again followed by desorption at 140 and 160 K, as these species are mixed into the ice matrix.…”
Section: Comet Grain Modelmentioning
confidence: 99%
“…For example, the values of the sublimation energies we use for H O 2 , NH 3 , CO 2 , and CO are 10%-20% higher than those derived from the very recent temperature programmed desorption experiments by Martín-Doménech et al (2014, see their Table 4). Luna et al (2014) compiled the sublimation energies of major cometary volatiles from different experimental methods, and showed that the published sublimation energies have a standard deviation of 14%, 8%, 11%, and 8% for NH 3 , CO 2 , CH 4 , and CO, respectively (see their Table 2 and Figures 4 and 5). Such uncertainties might be present in the vapor pressure data for other volatiles species.…”
Section: Equilibrium Vapor Pressuresmentioning
confidence: 99%
“…23.3-28.3 kJ mol −1 (He et al 2015). Quartz crystal microbalance techniques have also been used to investigate the sublimation of multilayer NH3 ice, yielding a sublimation energy of 31.8 kJ mol −1 (Luna et al 2014). In the case of silicate minerals incorporating one or other metal atoms, the resulting increase in potential adsorption sites would be expected to influence the adsorption energies of bound species.…”
Section: Introductionmentioning
confidence: 99%